Closed Incision Negative Pressure Wound Therapy Versus Standard Dressings in Obese Women Undergoing Cesarean Section: Multicenter Parallel Group Randomized Controlled Trial. Issue 2 (24th June 2022) - Gillespie, B.M.; Webster, J.; Ellwood, D.; Thalib, L.; Whitty, J.A.; Mahomed, K.; Clifton, .; Kumar, S.; Wagner, A.; Kang, E.; Chaboyer, W.
Abstract : ( BMJ . 2021;373:n893) Cesarean deliveries (CD) lead to increased risk for adverse maternal outcomes, especially for obese women. Obesity during pregnancy is common and increases the risk of postoperative complications such as surgical site infection (SSI), hematoma and seroma, and wound dehiscence. Use of closed incision negative pressure wound therapy (NPWT) dressings has increased in an effort to decrease SSI. This trial aimed to analyze how closed incision NPWT dressings compare with standard dressings in obese women following CD.